Comparison of oxygen therapy with simple face mask and nasal canola on hemoglobin oxygen saturation - Mokhtar Yaaghoobi; Daem Roshani; Alireza Gharib; Shabnam Khodadadi (Kurdistan University of Medical Sciences, 2016)
Introduction and Aims: one of the most common complications after surgery is hypoxia and it can create a lot of problems and complications for patients. This study aimed to determine the effect of oxygen therapy with simple face mask over and nasal canola on the hemoglobin oxygen saturation after the surgery in the recovery room. Materials and Methods: This study was performed on 84 patients in the recovery room of Besat hospital in Sanandaj city and the patients were randomly divided into two groups. Both groups were treated with nasal cannula and oxygen mask and received 5 liters of oxygen. Then, before and after the intervention the hemoglobin saturated of oxygen was measured and then were compared together. SPSS 23 was used for data analysis. In order to compare the mean of hemoglobin saturated of oxygen before and after intervention in both methods of simple face mask and nasal canola paired t-test was used and for the comparison of means before and after the intervention independent t-test was used. Results: The results showed that there was a significant difference in hemoglobin oxygen saturation before and after the treatment with nasal cannula and oxygen simple face mask (0.0001 Conclusion: The results of the findings showed that oxygen therapy had no influence on hemoglobin oxygen saturation in the two groups of simple face mask and nasal canola and the longer the time of receiving oxygen, the more the percentage of hemoglobin oxygen saturation.